The evaluation of a reductive pyrolysis reactor for the destruction of CFC-12, and the production of HCN - Faul, Charles Frederick James (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 1996.